Inflammatory and degenerative changes in the extensor pollicis longus muscle and tendon following ruptures caused by distal radius fractures - Christos Ni. Sarigiannis; Michael Ullman; Ingrid Andreasson; Anders Oldfors; Anders Björkman (BMC Musculoskeletal Disorders)
Abstract Background Rupture of extensor pollicis longus tendon (EPL) is a known complication following a distal radius fracture (DRF). Although the precise mechanisms behind these ruptures remain unclear, vascular impairment is thought to play a significant role. Additionally, the impact of an EPL rupture on microstructure of the tendon and muscle is not well understood, but such information could be important in guiding treatment strategies. This study aims to explore the histopathological changes in the EPL tendon and muscle in patients who have experienced an EPL rupture following a DRF. Methods Consecutive patients with an EPL rupture following a DRF were included and treated with an Extensor Indicis Proprius to EPL tendon transfer. Samples were taken from the distal part of EPL muscle and the proximal tendon from the musculotendinous junction to the rupture site as well as from the tendon distal to the rupture. The tendon specimens were analysed by standard histopathological techniques including immunohistochemistry. In cases of sufficient amount of muscle, fresh frozen specimens were analysed by enzyme- and immuno-histochemistry on cryostat sections. Results Thirteen patients (12 females, 1 male; median age 61, range 18–72 years) were included in the study. The EPL muscle in all participants showed extensive inflammatory changes, muscle fiber necrosis and regeneration, structural changes in the muscle fibers and slight interstitial fibrosis. The EPL tendon showed profound degenerative changes mainly in the central part of the tendon whereas there were regenerative changes in the periphery of the tendon. The pathological changes were present in all samples regardless of time between the DRF and the EPL rupture or the time between the diagnosis of the rupture and surgery. Conclusions The extensive inflammatory changes in the EPL muscle indicate that immune mediated mechanisms are involved in muscle degeneration following tendon rupture. The EPL tendon showed characteristic degenerative changes at the myotendinous junction, as well as proximally and distally to the rupture site. The reversibility and the clinical significance of the severe pathological changes seen in the EPL muscle alongside the healing potential of the tendon need further investigation. Trial registration Retrospectively registered the 2024–03-15 at Clinicaltrials.gov, ID: NCT06313489.